Xiaoyu Xiezhuo Decoction Improves Diabetic Kidney Disease by Regulating Cysteine and Methionine Metabolism - Yuancheng Gao; Yue Ji; Xiang Zhang; Qi Liu; Xinnan Jin; Jiawen Qian; Ziyang Wu; Xiangfu Gao; Shouci Hu; Hongbo Chen (Journal of Diabetes Research)
Conclusion: XXD alleviates renal injury in DKD mice by exerting anti-inflammatory and antioxidant effects through the modulation of the cysteine and methionine metabolism pathway.